2020
DOI: 10.1371/journal.pone.0231267
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific stress response and HMGB1 release in pulmonary endothelial cells

Abstract: Women are known to be associated with a higher susceptibility to pulmonary arterial hypertension (PAH). In contrast, male PAH patients have a worse survival prognosis. In this study, we investigated whether the contribution of sex goes beyond the effects of sex hormones by comparing the ability of isolated male and female pulmonary endothelial cells to respire, proliferate and tolerate the stress. Mouse lung endothelial cells (MLEC) were isolated from the lungs of male and female 3-week old mice. Male MLEC sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 48 publications
2
30
0
Order By: Relevance
“…Sex-related differences in immune responses can lead to differential mode of action to clear the viral load and damaged cells. Stressed pulmonary endothelial cells in males are known to undergo necrosis while in females apoptosis is more common [71]. Since necrosis releases more HMGB1 than apoptosis [71], this indicates that HMGB1 levels are differentially regulated in male and female COVID-19 patients with higher levels in males that further contributes to the severity and high mortality in males.…”
Section: Immune System Differences and Viral Infectionmentioning
confidence: 99%
“…Sex-related differences in immune responses can lead to differential mode of action to clear the viral load and damaged cells. Stressed pulmonary endothelial cells in males are known to undergo necrosis while in females apoptosis is more common [71]. Since necrosis releases more HMGB1 than apoptosis [71], this indicates that HMGB1 levels are differentially regulated in male and female COVID-19 patients with higher levels in males that further contributes to the severity and high mortality in males.…”
Section: Immune System Differences and Viral Infectionmentioning
confidence: 99%
“…A recent study demonstrated an unexpected genderspecific stress response and HMGB1 release in isolated murine pulmonary endothelial cells (Zemskova et al 2020). These cells from males were more sensitive than those from females to hypoxia and impaired mitochondrial function to which they responded by necrotic death.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that P. falciparum parasites or parasite products trigger signalling pathways in innate immune cells from females but not males. It is known that the necrotic or necroptotic pathway of cell death which results in the release of HGMB1 by dying cells occurs only in females (23). The relevance of this mechanism to our findings in Ugandan infants with malaria remains to be determined.…”
Section: Discussionmentioning
confidence: 99%